Entrepreneurship Promotion in Higher Education Institutions - Sousa, Áurea; Couto, Gualter; Branco, Nélia; Silva, Osvaldo; Bacelar-Nicolau, Helena (Journal of Entrepreneurship, Business and Economics, 2016)
Abstracts The importance of entrepreneurship promotion has increased significantly in today's society, especial-ly during periods of crises. This work is based on the responses obtained through a survey conducted on a sample of 305 undergraduates of the University of the Azores, enrolled in different science pro-grams. The aim is to deepen the knowledge of the entrepreneurial propensity of higher education students in the Azores, and in that way the university can stimulate their interest in creating business-es. The main results obtained, using exploratory data analysis (from the univariate to the multivari-ate), are presented and discussed. Research paper Reference to this paper should be made as follows: Sousa, Á., Couto, G., Branco, N., Silva, O., Bace-lar-Nicolau, H. (2017). “Entrepreneurship Promotion in Higher Education Institutions”, Journal of Entrepreneurship, Business and Economics, Vol. 5, No. 1, pp. 157–184.